看護師の終末期がん患者と家族間の対話支援自己評価尺度の開発 - 浅野 志保; 古瀬 みどり (日本看護科学会誌, 2023)
要旨　目的：看護師の終末期がん患者と家族間の対話支援自己評価尺度を開発し，信頼性と妥当性を検討することを目的とした．　方法：全国の臨床経験3年以上の看護師1,196名に対し，看護師の終末期がん患者と家族間の対話支援に関する自己評価尺度38項目を含むオンライン調査を実施した．統計解析では，探索的因子分析を行い，内的一貫性と構成概念妥当性を検討した．　結果：有効回答370件（30.9％）を分析した．探索的因子分析の結果，4因子22項目が抽出された．Cronbach's α係数は尺度全体.944，下位尺度.797〜.908であった．モデル適合度は，GFI＝.888，AGFI＝.860，CFI＝.931，RMSEA＝.063であった．収束的妥当性はr＝.819，併存的妥当性はr＝.403であった．　結論：4因子22項目が抽出され，本尺度の信頼性と妥当性が検証された． 　Purpose: This study aimed to examine the reliability and validity of a self-assessment scale for nurses to enhance dialogue support between terminally ill cancer patients and their families.　Methods: Subjects were 1,196 nurses with at least 3 years of clinical experience working at hospitals throughout Japan, and who were involved in the care of terminally ill cancer patients. An online questionnaire was administered, which included 38 items on a self-assessment scale for nurses' support of dialogue between terminally ill cancer patients and their families. The statistical analysis included exploratory factor analysis, and examination of internal consistency and construct validity.　Results: A total of 370 responses (30.9％) were analyzed. An exploratory factor analysis helped identify four factors (22 items): (1) Assessing patients' and families' dialogue needs; (2) Focusing on patients and families for a deeper understanding of them; (3) Engaging with patients and families with respect for each other's feeling; and (4) Utilizing a team approach for dialogue support. Cronbach's alpha coefficient was .944 for the total scale and ranged from .797 to .908 for the four factors. The goodness of fit of the model was as follows: GFI＝.888, AGFI＝.860, CFI＝.931, and RMSEA＝.063. The known-groups technique was used to examine construct validity. The scale score showed significantly higher scores among groups with experience in a palliative care unit and among certified nurses or certified nurse specialists in oncology nursing. The convergent validity was .819 (p＜.01), concurrent validity was .403 (p＜.01).　Conclusions: This study's results suggest that the scale's validity and reliability were within the permissible range.